2016
DOI: 10.1111/rda.12717
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid Synthesis and its Receptors’ Expression in the Bovine Oviduct During the Oestrous Cycle

Abstract: Lysophosphatidic acid (LPA) is a naturally occurring simple phospholipid which in the bovine reproductive system can be produced in the endometrium, corpus luteum, ovarian follicle and embryo. In this study, we examined the possibility that LPA receptors are expressed, and LPA synthesized, in the bovine oviduct. We found that the concentration of LPA was highest in infundibulum in the follicular phase of the oestrous cycle and was relatively high during the early-luteal phase in all examined parts of the ovidu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
(109 reference statements)
0
5
0
Order By: Relevance
“…A significant immunoreaction of ATX, together with co-existing PLA 2 enzymes in oviductal epithelia, suggests rat oviductal cavity as a site of LPA production and/or secretion. The existence of LPA producing machinery is partly supported by very recent and detailed studies with a bovine model by Woclawek-Potocka and Yamamoto’s groups [ 29 , 37 ]. They demonstrated expression of mRNAs for ATX, group IVA PLA 2 , and PLA 1 α in epithelial and stromal cells and LPA content in oviductal tissues.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A significant immunoreaction of ATX, together with co-existing PLA 2 enzymes in oviductal epithelia, suggests rat oviductal cavity as a site of LPA production and/or secretion. The existence of LPA producing machinery is partly supported by very recent and detailed studies with a bovine model by Woclawek-Potocka and Yamamoto’s groups [ 29 , 37 ]. They demonstrated expression of mRNAs for ATX, group IVA PLA 2 , and PLA 1 α in epithelial and stromal cells and LPA content in oviductal tissues.…”
Section: Discussionmentioning
confidence: 92%
“…However, ATX/LPA system in post-ovulation processes such as the dynamics of released COCs and fertilizing and dividing potential within the oviduct remains to be clarified. Very recent studies with a bovine model demonstrated mRNA expression of synthetic enzymes (ATX, Group IVA PLA 2 , and PLA 1 α) and signaling receptors (all LPA receptors except for LPA 5 ) in the oviduct [ 29 , 37 ]. Given these findings, we here focus on 1) expression of enzyme and receptor proteins in ovulated COCs and the oviduct and 2) possible in vivo functional role(s) of ATX/LPA system in COCs around fertilization in a rat model.…”
mentioning
confidence: 99%
“…LPA was found to be involved in gamete transport, fertilization and cell signal transmission between oviductal tissue and the cumulus oocyte complex [53,54]. LPAR2 was found to be abundantly expressed in the oviduct of cattle, suggesting that the oviduct is an important target of LPA [55]. Fibroblast growth factor 18 (FGF18) inhibits the secretion of estradiol and progesterone, and is a candidate factor that regulates steroidogenesis during ovarian development [56].…”
Section: Differential Expression Analysis and Functional Analysis Of Mirnasmentioning
confidence: 99%
“…LPA was found to be involved in gamete transport, fertilization, and cell signal transmission between oviduct tissue and cumulus oocyte complex [55,56]. And LPAR2 was found to be abundantly expressed in the oviduct of cattle, suggesting that the oviduct is an important target of LPA [57]. Fibroblast growth factor 18 (FGF18) inhibits the secretion of estradiol and progesterone, and is a candidate factor that regulated the steroidogenesis during ovarian development [58].…”
Section: Discussionmentioning
confidence: 99%